Cerebrospinal fluid in Borna disease virus 1 (BoDV-1) encephalitis - Neumann, Bernhard; Hierl, Andreas; Wunderlich, Silke; Meier, Helen; Bauer, Christina; Gerner, Stefan; Rieder, Georg; Geis, Tobias; Kunkel, Jürgen; Bauswein, Markus; Niller, Hans Helmut; Schmidt, Barbara; et al. (Journal of the Neurological Sciences, 2023)
Borna disease virus 1 (BoDV-1) has been recognized as a rare cause of very severe encephalitis with rapid onset in central Europe. Data on cerebrospinal fluid (CSF) analysis have not yet been analyzed in detail. Here, we present the first study on CSF changes in BoDV-1 encephalitis. We retrospectively analyzed CSFs from 18 BoDV-1 encephalitis cases from Bavaria, Germany, an endemic region, from 1996 to 2021. Data were obtained through review of medical records and institutional databases. We found that white blood cell count (WBC) in CSF is elevated in 13 of our 18 patients at first examination (average 83.2 ± 142.3 leukocytes/μl) and cytology showed predominance of lymphocytes. Patients with typical symptoms of meningoencephalitis had higher WBC in first CSF analyzation (133.5 ± 163.1 vs 4.0 ± 3.2/μl; p = 0.065). BoDV-1 PCR of CSF is not always positive when tested (7 of 9 cases). Four of five patients tested showed a polyvalent reaction against multiple viruses in the CSF suggesting that BoDV1 may trigger autoimmune mechanisms. CSF changes in BoDV-1 encephalitis seem similar to those of other viral encephalitis and at the beginning WBC can be normal in up to 28%, making the diagnosis even more challenging. All in all, BoDV-1 should be included in the diagnostic workup of patients with rapidly evolving and/or severe encephalitis and patients with severe neuropathy and secondary encephalopathy with and without CSF changes. Repeated CSF examinations as well as BoDV-1 serology and CSF PCR have to be considered in endemic areas.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Borna disease virus 1 (BoDV-1); Cerebrospinal fluid; Viral encephalitis